2018
DOI: 10.1186/s12876-018-0744-8
|View full text |Cite
|
Sign up to set email alerts
|

Gastric bacterial Flora in patients Harbouring Helicobacter pylori with or without chronic dyspepsia: analysis with matrix-assisted laser desorption ionization time-of-flight mass spectroscopy

Abstract: BackgroundThe gastric microbiota has recently been implicated in the causation of organic/structural gastroduodenal diseases (gastric and duodenal ulcers, gastric cancer) in patients with Helicobacter pylori (H. pylori) infection. We aimed to ascertain, in patients harbouring H. pylori, the role of the gastric microbiota in the causation of symptoms (chronic dyspepsia) in the absence of organic disease.MethodsSeventy-four gastric biopsy samples obtained at endoscopy from patients with (n = 21) or without (n = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 36 publications
1
16
1
Order By: Relevance
“…We cannot explain dominance of these species in relation to dyspepsia because each group harbored gram positive cocci and gram negative bacilli. Our reports about the significant difference in gastric microbiota in both groups dyspeptic and not dyspeptic is in agreement with Pereira et al, [8] who found qualitative difference in the gastric microbial spectrum between patients harbouring H. pylori with and without chronic dyspepsia .The prevalence comprised Staphylococcus followed by Lactobacillus in patients with H. pylori-positive chronic dyspepsia and by Streptococcus followed by Staphylococcus and Klebsiella in those without dyspepsia. Second, in fact our finding of the association between Lactobacillus with dyspepsia and H. pylori is not novel because Lactobacillus has been incriminated to have a role in progression to gastric cancer in presence of H. pylori infection [13].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…We cannot explain dominance of these species in relation to dyspepsia because each group harbored gram positive cocci and gram negative bacilli. Our reports about the significant difference in gastric microbiota in both groups dyspeptic and not dyspeptic is in agreement with Pereira et al, [8] who found qualitative difference in the gastric microbial spectrum between patients harbouring H. pylori with and without chronic dyspepsia .The prevalence comprised Staphylococcus followed by Lactobacillus in patients with H. pylori-positive chronic dyspepsia and by Streptococcus followed by Staphylococcus and Klebsiella in those without dyspepsia. Second, in fact our finding of the association between Lactobacillus with dyspepsia and H. pylori is not novel because Lactobacillus has been incriminated to have a role in progression to gastric cancer in presence of H. pylori infection [13].…”
Section: Discussionsupporting
confidence: 93%
“…The current study showed the species harvesting the inflamed gastric mucosa belongs to both gram positive and negative bacteria. The species isolated from the stomachs of our cohort are not different from the species reported in recent studies [8] recently published. We found Staphylococcus spp., Lactibacillus which belonged to phyla firmuicules and protebacteria [12] in our study, the flora in H. pylori positive patients with chronic dyspepsia was dominated by Staphylococcus and Lactobacillus and without dyspepsia showed dominance Streptoccous and Klebsilla.…”
Section: Discussioncontrasting
confidence: 46%
“…Staphylococcus and Lactobacillus were identified more significantly in dyspeptic patients and Streptococcus , Pseudomonas , Escherichia coli, and Klebsiella pneumoniae in nondyspeptic patients. All identified organisms belonged to the phyla Firmicutes and Proteobacteria . Thus, there is a qualitative difference in the gastric microbiota between patients harboring H. pylori with and without dyspepsia.…”
Section: Helicobacter Pylori Infection and Dyspepsiamentioning
confidence: 92%
“…These include two studies from India, two studies from Europe (UK and Austria) and single studies from China, Japan and Nicaragua. [33][34][35][36][37][38][39] Changes in the gastric microbiome were noted in all studies in response to H. pylori infection or different pathological states however other than H. pylori infection, there was no consistent gastric microbiome signature detected probably reflecting the importance of environmental influences. All studies noted reduced microbial diversity in H. pylori-infected groups, with one of the studies from India highlighting the ability of H. pylori to shape the constitution of the gastric microbiome but suggesting that other members of the Helicobacteraceae could also similarly influence community structure.…”
Section: Helicobacter Pylori and The Gastric Microbiomementioning
confidence: 87%
“…Several articles have also looked at the gastric microbiome in noncancerous and premalignant conditions as a result of H. pylori infection. These include two studies from India, two studies from Europe (UK and Austria) and single studies from China, Japan and Nicaragua . Changes in the gastric microbiome were noted in all studies in response to H. pylori infection or different pathological states however other than H. pylori infection, there was no consistent gastric microbiome signature detected probably reflecting the importance of environmental influences.…”
Section: Gastric Microbiomementioning
confidence: 93%